Albesd Fun Mart: Sinergi Kebhinekaan Global dan Edupreneurship sebagai Inovasi Pembelajaran P5 bagi Generasi Mandiri - Sekar Ayu; Ishaq Nuriadin (Jurnal Riset Pendidikan Matematika Jakarta, 2025)
This study discusses the implementation of the Pancasila Student Profile Strengthening Project (P5) with the theme of “Entrepreneurship” at SMA Islam Al-Azhar BSD as an integration of edupreneurship values in education. The activity, titled Albesd Fun Mart, involved 11th-grade students from various academic tracks who were divided into groups to showcase and sell country-themed products, such as food, fashion, and cultural items. The project was carried out through four stages: introduction, contextualization, action, and reflection. Observations and interviews revealed that the program positively impacted students’ entrepreneurial character development, including initiative, creativity, collaboration, and communication skills. Moreover, it supported contextual learning, strengthened 21st-century competencies, and increased student enthusiasm and ownership of their projects. However, several challenges were noted, such as unequal task distribution and limited financial management knowledge. Overall, the program provided meaningful experiential learning and can serve as a best practice model for entrepreneurship education.